Bank swallows in Canada's north : an interdisciplinary study - Bols, Sonje Helena (Nipissing University, Faculty of Arts & Science, 2017)
This thesis / dissertation was completed and submitted at Nipissing University, and is made freely accessible through the University of Toronto’s TSpace repository The Bank Swallow (Riparia riparia) is a globally-distributed migratory species that has seen population declines of 98 % on their Canadian breeding grounds. Not a lot is known about their historic populations or nesting behaviour in northern Canada, near their northern range limit. In this study, I use an interdisciplinary approach to address these knowledge gaps by examining the Bank Swallow?s historic distribution in northern Ontario as well as conducting a field study of a breeding population in the Yukon Territory. I monitored the nesting activity of this species using video recordings in the Whitehorse, YT region and examined the activity of adults at burrow entrances in relation to a variety of nest site characteristics including nest bank height, aspect and soil type, as well as nearby foraging habitats. Video recordings of 30 min during the incubation and fledging periods were highly effective at recording nesting activity and could be useful for monitoring Bank Swallow populations in an affordable and repeatable manner. Foraging habitat diversity was significantly higher near active colonies compared to inactive colony sites. Adult activity at burrows was positively related to habitat diversity, likely because diverse habitats provide more foraging opportunities for insect prey. A critical examination of historic records of this species in northern Ontario revealed a wide and well-surveyed provincial distribution and a trend for colony sites to be found most commonly in anthropogenic sites, especially within Algonquin Provincial Park. This study also provides a method for gaining useful historic distribution data from wildlife specimens and records, plentiful in museums across North America. M.E.Sc.